2020
DOI: 10.3389/fnmol.2020.00164
|View full text |Cite
|
Sign up to set email alerts
|

Dystroglycan Mediates Clustering of Essential GABAergic Components in Cerebellar Purkinje Cells

Abstract: Muscle dystrophin–glycoprotein complex (DGC) links the intracellular cytoskeleton to the extracellular matrix. In neurons, dystroglycan and dystrophin, two major components of the DGC, localize in a subset of GABAergic synapses, where their function is unclear. Here we used mouse models to analyze the specific role of the DGC in the organization and function of inhibitory synapses. Loss of full-length dystrophin in mdx mice resulted in a selective depletion of the transmembrane β-dystrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 65 publications
3
31
1
Order By: Relevance
“…In addition, α2- and γ2 -GABA A Rs and miniature IPSC frequency are normal in hippocampal cultures from the gephyrin knock-out [ 85 ]. Gephyrin-independent clustering of GABA A Rs has been observed in other brain areas, including α1-containing GABA A Rs on Purkinje cell somas [ 86 , 87 , 88 , 89 ], perisomatic α1-containing GABA A Rs on hippocampal Pyr cells [ 90 , 91 , 92 ], and α2/α3/α5/β3-containing GABA A Rs on sensory afferents [ 93 ]. Our data indicate that gephyrin may be a particularly unreliable marker for PV-type inhibitory synapses and suggest that other types of inhibitory inputs be carefully evaluated for gephyrin colocalization.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, α2- and γ2 -GABA A Rs and miniature IPSC frequency are normal in hippocampal cultures from the gephyrin knock-out [ 85 ]. Gephyrin-independent clustering of GABA A Rs has been observed in other brain areas, including α1-containing GABA A Rs on Purkinje cell somas [ 86 , 87 , 88 , 89 ], perisomatic α1-containing GABA A Rs on hippocampal Pyr cells [ 90 , 91 , 92 ], and α2/α3/α5/β3-containing GABA A Rs on sensory afferents [ 93 ]. Our data indicate that gephyrin may be a particularly unreliable marker for PV-type inhibitory synapses and suggest that other types of inhibitory inputs be carefully evaluated for gephyrin colocalization.…”
Section: Discussionmentioning
confidence: 99%
“…Clstn3 protein was localized to parallel-fiber synapses by immunoelectron microscopy (Hintsch et al, 2002). Moreover, other genetic manipulations that cause a decrease in inhibitory synaptic transmission in cerebellar cortex, such as deletions of Nlgn2 or of GABA A -receptors (Briatore et al, 2020; Fritschy et al, 2006; Meng et al, 2019; Zhang et al, 2015), do not induce an increase in excitatory parallel-fiber synapses. Finally and probably most importantly, although competition between synapses using the same transmitters is well-described (e.g., competition between glutamatergic parallel- and climbing-fiber synapses on Purkinje cells; Cesa and Strata, 2009; Miyazaki et al, 2012; Strata et al, 1997), no such competition has been observed between GABAergic and glutamatergic synapses, such that the decrease in one of them would lead to the increase of the other.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of presynaptic neurexins with cerebellins and postsynaptic GluD receptors plays a major role in shaping parallel-fiber synapses (Yuzaki and Aricescu, 2017), and the binding of C1ql1 to postsynaptic Bai3 has a prominent function in climbing-fiber synapses (Kakegawa et al, 2015; Sigoillot et al, 2015). Postsynaptic Nlgn2 and Nlgn3 are major contributors to the function of GABAergic synapses in Purkinje cells (Zhang et al, 2015), as is dystroglycan (Briatore et al, 2020). How can we envision the collaboration of various synaptic adhesion complexes in establishing and shaping the different types of synapses on Purkinje cells?…”
Section: Discussionmentioning
confidence: 99%
“…While this is the only demonstration, to our knowledge, of a complete recycling loop of an ECM molecule, many additional studies also add credence to the concept of ECM recycling at synapses. These include reports of ECM molecules that undergo internalization (e.g., Coopman et al, 1996 ; Tammi et al, 2001 ; Shi and Sottile, 2008 ; Lobert et al, 2010 ; Leonoudakis et al, 2014 ), demonstrations that ECM receptors are present at synapses (e.g., Kramár et al, 2002 ; Huang et al, 2006 ; Roszkowska et al, 2016 ; Izumi et al, 2017 ; Apóstolo et al, 2020 ; Briatore et al, 2020 ), and reports that synapses contain the machinery for trafficking recycling molecules in an activity-dependent manner (Tang, 2008 ; Gürth et al, 2020 ; Helm et al, 2021 ). Nevertheless, additional demonstrations of the recycling of ECM molecules in neurons are anticipated in the future.…”
Section: Recycling Of Synaptic Ecmmentioning
confidence: 99%